Pengelolaan Berkas Rekam Medis Pasien Rawat Inap Bangsal Mawar di RSUP Dr. Tadjuddin Chalid Makassar - Hasmah Hasmah; Musfirah Musfirah; Syamsiana Syamsiana (J-KESMAS: Jurnal Kesehatan Masyarakat, 2022)
Medical record file management is the activity of assembling and completing the filling (analysis) of medical record files and giving disease codes (coding), indexing grouping (indexing) and storing medical record files (filling) in accordance with the provisions. Regulation of the Minister of Health which stipulates that the activities of organizing medical records are carried out on all medical services and actions provided to patients, both outpatients, inpatients, and emergency departments. This study aims to determine the management of inpatient medical record files in the Mawar ward. The research was conducted using quantitative research methods with a descriptive approach. This research was carried out at the Medical Record Installation of Dr. Tadjuddin Chalid Makassar. The population and samples were 93 medical record files. The presentation of the data is done in the form of a distribution table accompanied by an explanation after going through quantitative data analysis using a checklist instrument. The results showed that assembling, analysis and filling were below 80%, while indexing and coding were 100%. The conclusion from the research is that assembling, analyzing and filling have not met the quality standards of hospital services. Meanwhile, coding and indexing have met the quality standards of hospital services. It is recommended that there be an increase and additional personnel, especially in the analysis section and for the coding section, even though they have met the quality standards of hospital services, they need training and always follow the socialization related to the applicable ICD